Anatomical and ultrastructural studies reveal temporal and spatial variation in the oil production in leaves of the diesel tree (Copaifera langsdorffii, Leguminosae) - Buarque, Plácido Fabrício Silva Melo [UNESP]; Machado, Silvia Rodrigues [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Springer Nature, 2020)
The oily resin produced by Copaifera langsdorffii, commonly called oil of copaiba, is widely exploited by the drug, cosmetic, and biodiesel industries. The distribution of oily secretory cavities and canals (secretory spaces) over the vegetative body characterizes this species. Oil is stored inside the lumen of the secretory spaces and only reaches the organ surface after injuries. Nonetheless, translucent oily deposits occur on the adaxial surface of intact young leaves. In this study, we searched for further sources of oil production in C. langsdorffii leaves in addition to the well-known secretory cavities and investigated the mechanisms of secretion. Leaves in different developmental stages were collected from adult plants and processed for studies on light and transmission electron microscopies. The primary finding of this study was the involvement of the chlorenchyma cells in lipid biosynthesis, in addition to the secretory cavities. The secretory activity of cavities and chlorenchyma cells overlapped in young leaves. Ultrastructurally, secretory cavity cells exhibited abundant smooth endoplasmic reticulum profiles and oleoplasts, whereas the chlorenchyma cells had large chloroplasts with oil inclusions. Our data suggest that the oily material on the leaf surface arose from the chlorenchyma and was transported via the apoplast. These findings open new avenues for understanding oil biosynthesis regulation in mesophyll cells and planning of future strategies for the biotechnological application of C. langsdorffii leaves.
Keywords: Cell ultrastructure; Copaiba; Leaflet; Oil biosynthesis; Secretory cavity; Secretory chlorenchyma